Peningkatan Kompetensi Bermain Drama dengan Metode Lavonte - Widiastuti, Yuanita; Arrozaq, M. Fadlulloh; Ambarwati, Ari (ppjbsip, 2022)
Drama performances performed by students of class XI SMA have a lack of self-confidence, to overcome this the researcher applies the Lavonte method, namely vocal exercises, and expression therapy. This study aims to make students of class XI MIPA 1 SMAN 1 Kraksaan able to improve their competence in expressing the dialogue of the characters in drama performances using the Lavonte method. The sample of this study consisted of 32 students. Indonesian language subject, basic competence